Learning from Results-Based Management evaluations and reviews - Vähämäki, Janet; Verger, Chantal (OECD, 2019)
What have we learned from implementing results-based management in dev elopment co-operation organisations? What progress and benefits can be seen? What are the main challenges and unintended consequences? Are t here good practices to address these challenges? To respond to these q uestions this paper reviews and analyses the findings from various eva luations and reviews of results-based management systems conducted by members of the Development Assistance Committee (DAC), the OECD/DAC Re sults Community Secretariat and other bodies in the past four years (2 015-2018). It also draws on emerging lessons from new methods for mana ging development co-operation results. This analytical work aims to: i dentify recent trends in results-based management, explore challenges faced by providers when developing their results approaches and system s, select good practices in responding to these challenges that can be useful for the OECD/DACResults Community, considering new approaches, new technologies and evolving contexts. This body of evidence will in form the development of a core set of generic guiding principles for r esults-based management in development co-operation.